Impact of coronary calcification on outcomes after ABSORB scaffold implantation: insights from the GABI-R registry. Issue 7 (November 2020) - Hemetsberger, Rayyan; Abdelghani, Mohammad; Mankerious, Nader; Allali, Abdelhakim; Toelg, Ralph; Gori, Tommaso; Achenbach, Stephan; Riemer, Thomas; Mehilli, Julinda; Nef, Holger M.; Naber, Christoph; Wöhrle, Jochen; et al.
Abstract : Objective: To investigate the outcomes after bioresorbable scaffold (BRS) implantation in calcified coronary lesions. In calcified coronary lesions, durable metallic drug-eluting stent (DES) implantation is associated with worse clinical outcomes compared to noncalcified lesions. Although not recommended, BRSs were frequently implanted in calcified lesions in clinical practice. Their outcome is not well investigated. Methods: Between November 2013 and January 2016, 3326 patients were enrolled in the German-Austrian ABSORB ReglstRy (GABI-R). Lesion calcification severity was classified into no ( n  = 1144), mild ( n  = 1306), and moderate-to-severe ( n  = 690) calcification. Results: Patients with calcification were older (none: 59.1 ± 11.2 vs. mild: 61.6 ± 10.9 vs. moderate to severe: 62.4 ± 10.5 years, P  < 0.001), had more diabetes (19.1 vs. 20.8 vs. 23.9%, P  = 0.015), and more often had previous myocardial infarction (MI) (19.3 vs. 23.1 vs. 25.4%, P  = 0.002). Despite a higher rate of postdilatations ( P  < 0.001), lesions with calcification had more residual stenosis (2.05 ± 9.36% vs. 3.11 ± 9.36% vs. 3.89 ± 9.39%, P  < 0.001). Consequently, procedural success was achieved in 97.7 vs. 96.2 vs. 93.6% of cases in none, mild, and moderate-to-severe calcification ( P  < 0.001). At 24 months, cardiac death (0.3 vs. 0.7 vs. 1.6%, P  = 0.009) was higher with increasing calcification. However, no significant between-group difference was observed in the incidence of target vessel MI, target vessel revascularization, or target lesion failure. The rate of probable scaffold thrombosis was significantly higher with increasing calcification. Conclusion: In GABI-R, ABSORB scaffolds in calcified lesions required more postdilation, led to more residual stenosis, but did not portend increased target lesion revascularization over 2 years. Nevertheless, coronary calcification severity emerged as a cardiovascular risk marker and was predictive of cardiovascular mortality. Clinicaltrial.gov NCT02066623. Abstract : Supplemental Digital Content is available in the text.